Dynamic Expression of HDAC3 in db/db Mouse RGCs and Its Relationship with Apoptosis and Autophagy - Yuhong Fu; Ying Wang; Xinyuan Gao; Huiyao Li; Yue Yuan (Journal of Diabetes Research)
Background. Diabetic retinopathy (DR) is a severe complication of diabetes mellitus. DR is considered as a neurovascular disease. Retinal ganglion cell (RGC) loss plays an important role in the vision function disorder of diabetic patients. Histone deacetylase3 (HDAC3) is closely related to injury repair and nerve regeneration. The correlation between HDAC3 and retinal ganglion cells in diabetic retinopathy is still unclear yet. Methods. To investigate the chronological sequence of the abnormalities of retinal ganglion cells in diabetic retinopathy, we choose 15 male db/db mice (aged 8 weeks, 12 weeks, 16 weeks, 18 weeks, and 25 weeks; each group had 3 mice) as diabetic groups and 3 male db/m mice (aged 8 weeks) as the control group. In this study, we examined the morphological and immunohistochemical changes of HDAC3, Caspase3, and LC3B in a sequential manner by characterizing the process of retinal ganglion cell variation. Results. Blood glucose levels and body weights of db/db mice were significantly higher than that of the control group, P<0.01. Compared with the control group, the number of retinal ganglion cells decreased with the duration of disease increasing. HDAC3 expression gradually increased in RGCs of db/db mice. Caspase3 expression gradually accelerated in RGCs of db/db mice. LC3B expression dynamically changed in RGCs of db/db mice. HDAC3 was positively correlated with Caspase3 expression (r=0.7424), P<0.01. HDAC3 was positively correlated with LC3B expression (r=0.7336), P<0.01. Discussion. We clarified the dynamic expression changes of HDAC3, Caspase3, and LC3B in retinal ganglion cells of db/db mice. Our results suggest the HDAC3 expression has a positive correlation with apoptosis and autophagy.